Finding the Gods in Public School: A Christian Deconstruction of Character Education - Glanzer, Perry L. (Journal of education & Christian belief, 2000)
MORAL EDUCATION IN American public schools is inextricably intertwined with and influenced by various religious and secular narratives. Character education is a prime example. Although it attempts to find some shared virtues within a pluralistic society, a historical overview and a Christian deconstruction of the movement reveals the illusionary nature of this agreement. In reality, character education often smuggles particular narratives into public schools that are antagonistic to other religious or secular narratives. Recognition of this fact should lead educators to make serious adjustments in moral education within public schooling and in the structure of public schooling.